2019
DOI: 10.1021/acs.jctc.9b00481
|View full text |Cite
|
Sign up to set email alerts
|

Improving Predicted Nuclear Magnetic Resonance Chemical Shifts Using the Quasi-Harmonic Approximation

Abstract: Ab initio nuclear magnetic resonance chemical shift prediction plays an important role in the determination or validation of crystal structures. The ability to predict chemical shifts more accurately can translate to increased confidence in the resulting chemical shift or structural assignments. Standard electronic structure predictions for molecular crystal structures neglect thermal expansion, which can lead to an appreciable underestimation of the molar volumes. This study examines this volume error and its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 96 publications
1
14
0
Order By: Relevance
“…The molar volume of typical organic crystals expands several percent upon heating from 0 K to room temperature. 91 This expansion alters the lattice energy and introduces anharmonicity into the phonons. Accounting for it is important for quantitatively comparing thermochemistry, 82,92-94 mechanical properties, 93 and spectroscopic observables 91,95 between theory and experiment.…”
Section: Theory and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The molar volume of typical organic crystals expands several percent upon heating from 0 K to room temperature. 91 This expansion alters the lattice energy and introduces anharmonicity into the phonons. Accounting for it is important for quantitatively comparing thermochemistry, 82,92-94 mechanical properties, 93 and spectroscopic observables 91,95 between theory and experiment.…”
Section: Theory and Methodsmentioning
confidence: 99%
“…96 The quasi-harmonic approximation is oen successfully used to approximate the volumedependent contributions to the phonons and lattice energies. 13,23,28,82,[91][92][93][94][97][98][99][100] Nevertheless, quasi-harmonic calculations remain considerably more expensive than purely harmonic calculations that neglect thermal expansion.…”
Section: Theory and Methodsmentioning
confidence: 99%
“…Recently, the fragment-based many-body expansion method (truncated at the two-body level) with embedding has been applied to compute the chemical shifts ( 1 H, 13 C, 15 N, and 17 O) of molecular crystals containing small molecules. Good results have been obtained with various density functionals and Gaussian basis sets. Nevertheless, it is unclear whether the same protocol without higher order (3- or 4-body) terms is accurate enough for solution systems, since energy calculations of large water clusters showed that 3- or 4-body interactions are still nontrivial …”
Section: Introductionmentioning
confidence: 99%
“…36,37 Fragment methods have also proved highly effective in molecular crystals. [38][39][40][41][42][43][44][45] Many of the fragment approaches can be unified under a common framework of a generalized many-body expansion, 46,47 with key distinctions between methods involving whether the fragments overlap or not, the level of interactions between fragments considered explicitly (e.g. are properties computed only on individual fragments or also with pairwise or higher-order interactions?…”
Section: Introductionmentioning
confidence: 99%